Rough Pythagorean Fuzzy Sets in UP-Algebras (European Journal of Pure and Applied Mathematics, 2022)
This paper aims to apply the concept of rough sets to Pythagorean fuzzy sets in UP-algebras. Then we introduce fifteen types of rough Pythagorean fuzzy sets in UP-algebras and study their generalization. In addition, we will also discuss $t$-level subsets of rough Pythagorean fuzzy sets in UP-algebras to study the relationships between rough Pythagorean fuzzy sets and rough sets in UP-algebras.
Keywords: UP-algebra; Pythagorean fuzzy set; Upper approximation; Lower approximation; Rough set; Rough Pythagorean fuzzy set; $t$-level subset